Excellent gas-sensitive properties towards acetone of In2O3 nanowires prepared by electrospinning - Che, Yanhan; Feng, Guoqing; Sun, Tianjun; Xiao, Jingkun; Guo, Weijun; Song, Chengwen (Colloid and interface science communications, 2021)
In2O3 nanowires (NWs) were successfully synthesized by electrospinning. The crystalline phase, microstructure, morphology, elemental composition, and BET surface area were analyzed XRD, SEM, TEM, XPS, and nitrogen adsorption. The characterization of the In2O3 NWs showed that In2O3 NWs were uniform thickness, structural integrity, and high purity. In subsequent gas-sensitive tests, the effects of PVP percentage, calcination temperature, calcination ramp-up rate, and calcination time on sensitive properties were analyzed. In particular, the In2O3 sensor showed a response of up to 37.9 (Ra/Rg) to 100 ppm acetone at an operating temperature of 200 °C and the response/recovery time is 1 s/7 s. The gas-sensitive mechanism of the In2O3 sensor was also analyzed in conjunction with the characterization results. Our study shows that the response of the In2O3 sensor is improved compared to the previously published sensors. [Display omitted] •In2O3 nanowires with uniform diameter, stable structure, and high BET surface area were synthesized by electrostatic spinning.•This In2O3 sensor shows an ultra-fast response to acetone gas and is highly sensitive.•The In2O3 sensor has a significant selectivity for acetone compared to several other volatile gases.